Penilaian Kinerja Sebagai Penentu Prestasi dan Kinerja Tenaga Kependidikan: Literature Review - Okvi Maharani; Ida Rindaningsih (MAMEN: Jurnal Manajemen, 2023)
In an organizational institution, in this case an educational institution, every employee is always demanded to be able to provide positive and best performance. This is a strong foundation that an institution's performance is very dependent on the performance of its employees. Therefore, with an objective evaluation of employee performance, it is hoped that it will be able to provide more encouragement to employees to work well. But what happens in many educational institutions, employee performance appraisal is still done manually, that is, based on certain standards or criteria, without regard to other criteria. This study analyzes the process of performance appraisal in educational institutions that are able to improve the performance of these institutions. The purpose of this research is to find out how far the performance appraisal process can improve achievement and performance in educational institutions. The method used in this study is an exploratory approach by reviewing the contents or identifying several articles. The results of the study show that objectively evaluating the performance of educational staff can improve their achievements and performance.